Relationship development : a micro-foundation for the internationalization process of the multinational business enterprise - Vahlne, Jan-Erik; Bhatti, Waheed Akbar (Springer Nature, 2018)
The interplay between knowledge development and commitments is the driving force in the Uppsala internationalization process model. We perform a qualitative thematic analysis of longitudinal data, exploring how relationship knowledge development in supplier-customer relationships leads to commitments through opportunity identification. The results validate our claim that relationship knowledge development as a dynamic capability can influence the focal organization’s ability to over time, under changing needs and contexts, harness operational capabilities that lead to at least satisfactory performance. Judging from results, the relationship knowledge development process produces a change in commitments, thereby constituting a critical micro-foundation for the internationalization and evolution process as explained in the Uppsala model.
Keywords: dynamic capabilities; internationalization process; relationship knowledge development process; Uppsala model; fi=Kansainvälinen liiketoiminta|en=International Business|